Feltarbeid som metodologisk utfordring i framtidas analyser av gehørtraderte musikkulturer - Larsen, Ove (Universitetsforlaget, 2007)
Postprint-versjon av artikkel publisert i Studia Musicologica Norvegica. Originalartikkel tilgjengelig på URL: http://www.idunn.no/ts/smn/2007/01/feltarbeid_som_metodologisk_-utfordring_i_framtidas_analyser_av_gehortrader This article discusses how fieldwork has been a central method for analysing and understanding music as part of culture. The author describes issues of understanding. Keywords:Fieldwork,music,ethnomusicology,oral tradition. and describing music via traditional fieldwork methods to modern use of Internet.